Digital Transformation in Museum Management: The Usage of Information and Communication Technologies - PARSEHYAN, BESTE GÖKÇE (ASOS Eğitim Bilişim Danışmanlık Otomasyon Yayıncılık Reklam Sanayi ve Ticaret LTD ŞTİ, 2020)
Today, museums are undergoing a process of digital transformation. Those museums able to properly manage this process will hold the potential of following and analyzing consumer perceptions and emotions. Information and Communication technologies are an important part of this digital transformation. This study aims to put forth the relationship between digital technologies and museums in terms of participatory technologies. The focus of the study will analyze at which stage private museums in Istanbul are at in the digital transformation process. The study is made up of three steps in order to measure the level at which museums utilize information and communication technologies. The first step takes place prior to the museum visit and analyzes the museums’ corporate websites. The second step is in relation to the visit of the museum, and defines the information and communication technologies available for visitors. The final step determines the social media presence of the museums after the visitation. The study analyzes the degree to which information and communication technologies are used by museums under the supervision of Turkey’s Ministry of Culture and Tourism’s General Directorate for Cultural Heritage and Museums in Istanbul. As a result of the study,the museums have been categorized under four categories: sleepers, social-oriented, visit-oriented and experience-oriented. Of the 62 museums within the framework of the study, 24% are sleepers, 36% social-oriented, 24% visit-oriented and 16% are experience-oriented. It is believed that the study will serve as a guide for museums which took part in the study so that they can increase the participatory experience of visitors.
Müze Yönetiminde Dijital Dönüşüm: Bilgi ve İletişim Teknolojilerini Kullanma Düzeyleri
Keywords: Management; Museum Management; Digital Transformation; Information and Communication Technologies; Digital Museums; / Yönetim; Müze Yönetimi; Dijital Dönüşüm; Bilgi ve İletişim Teknolojileri; Dijital Müzeler